THE CRITICAL LITERACY ROLE IN THE DEVELOPMENT OF CRITICAL THINKING SKILLS IN HIGH SCHOOL STUDENTS: AN INTERDISCIPLINARY APPROACH - Arifin, Syaadiah (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Critical thinking skills are an important aspect of education which enables students to analyze information critically and objectively. This journal article reviews the role of critical literacy in developing critical thinking skills in high school students through an interdisciplinary approach. Through the literature review method, this article explores the concepts of critical literacy and critical thinking skills and their relationship in the context of high school education. Critical literacy allows students to develop a deeper understanding of the information they encounter, while critical thinking skills enable them to critically evaluate that information and build strong arguments. The interdisciplinary approach highlights the importance of integrating diverse subjects in developing students' critical thinking skills. In this context, this article highlights the implications and challenges of integrating critical literacy in the school curriculum. It is hoped that this article can provide valuable insights for educators and policy makers in improving critical learning at the high school level.